Meta‐analysis of the incidence and patterns of second neoplasms after photon craniospinal irradiation in children with medulloblastoma. Issue 8 (25th April 2018) - Bavle, Abhishek; Tewari, Sayani; Sisson, Amy; Chintagumpala, Murali; Anderson, Michael; Paulino, Arnold C.
Abstract: Background: Second neoplasms (SNs) are a well‐established long‐term adverse effect of radiation therapy (RT), but there are limited data regarding their incidence and location relative to the radiation field, specific to medulloblastoma (MB) survivors after craniospinal irradiation (CSI). Methods: A systematic literature review, per Preferred Reporting Items for Systematic Reviews and Meta‐Analyses, identified six studies reporting the incidence and locations of SNs for 1, 114 patients with MB, after CSI, with a median follow‐up of ∼9 years (7.6–15.4 years). The study‐specific cumulative incidence (CI) of SNs, second benign neoplasms (SBNs), and second malignant neoplasms (SMNs) were standardized to a 10‐year time frame. Meta‐analysis was performed using random effects models, with pooled data from selected studies and an institutional cohort of 55 patients. Results: The 10‐year CI was 6.1% for all SNs (excluding skin cancer and leukemia), 3.1% for SBNs, and 3.7% for SMNs. Fifty‐eight percent of SNs were malignant; high‐grade glioma was the most common SMN (15/33; 45%) and meningioma, the most common SBN (16/24; 67%). Forty percent of SNs occurred outside the target central nervous system (CNS) field, with a majority in areas of exit RT dose. Seventy‐four percent of extra‐CNS tumors (17/23) were malignant, most commonly thyroid carcinoma (7/17; 41%) and bone and soft‐tissue tumors (6/17, 35%). Conclusions: Survivors of MB are at risk of SNs both within and outside the CNS. A significant proportion of SNs occur in areas of exit RT dose. Studies are needed to determine whether the use of proton therapy, which has no exit RT dose, is associated with a lower incidence of SNs.